An evaluation of degradable protein and nonprotein nitrogen on intake and digestion by Dohne merino sheep fed wheat straw - Nolte, Joubert van Eeden (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2000.